Pemodelan PM2,5 pada Musim Kemarau menggunakan Software Graz Lagrangian Model di Kecamatan Kota Baru, Kota Jambi - Alviani, Mayra; Anggraini, Febri Juita; Rodhiyah, Zuli (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Particulate Matter 2.5 (PM2.5) is one type of pollutant with a size of less than 2.5 microns which can cause increased mortality due to exposure. PM2.5 can be generated from natural activities, motor vehicles, industrial activities, and household activities. PM2.5 in Jambi City continues to increase from year to year until it is included in the dangerous category in 2019, with a concentration of 39.25 g/m3. Graz Lagrangian Model (GRAL) is an application that can model air pollution by entering meteorological data and pollutant concentrations. This study aims to determine the results of measuring the concentration of PM2.5 in Kota Baru District, Jambi City during the dry season and its comparison with the applicable quality standards and to model the distribution of PM2.5 in the Jambi City area using GRAL. The research was conducted in Simpang Tiga Sipin Village, Kota Baru District, Jambi City. In this study, measurements were carried out 3 times per month on weekdays for 72 hours. It is known that the average concentration of PM2.5 during the months of May, June, July and August 2021, respectively, is 30.32 μg/m3, 63.29 μg /m3, 43.66 μg/m3, and 26.26 μg/m3. The GRAL simulation results show that the areas that are often exposed to PM2.5 are Alam Barajo, Telanaipura, and Danau Sipin Districts.